Morphometric properties of larynx and trachea in the new zealand rabbit - Sema Özkadif; Mustafa Orhun Dayan; Yasin Demiraslan; Mevlüt Aykut; Özcan Özgel (Eurasian Journal of Veterinary Sciences)
Aim: This study was conducted to investigate the morphometric features of the larynx cartilages and trachea in New Zealand rabbits and reveal the differences between sexes. Material and Methods: In the study, the larynx cartilages belonging to a total of 12 healthy and adult New Zealand rabbits of both sexes (6 males, 6 females) were used. Some measurements were taken on the larynx cartilages and trachea, which had been taken out as a result of dissection of the head and neck, and statistical analyses were made. The statistical significance level was established at P<0.05. Results: Although the trachea and laynx related-measurements have no statistical difference between sexes, there was a statistical significance between sexes only in some values concerning the thyroid cartilage. Conclusion: In conclusion, it has been suggested that the results from this study will contribute to the present morphological knowledge on respiratory system and may shed light on the reconstructive anatomy and clinical procedures concerning this system.